Analisa Perhitungan Timbunan Maindam Pada Proyek Bendungan Cipanas Kab. Sumedang Paket 3 Menggunakan Metode Cross Section - Ayu Lestari, Diah; Hendrayana, Yayat; Toruan, Erni Sari Lumban (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
The purpose of this research is to know the calculation of the main dam volume in the Cipanas Dam Development Project, Kab. Sumedang Package 3 uses the Cross-Section Method, knowing the calculation of the productivity of the heavy equipment used, and knowing the stages of carrying out the main dam embankment work.The method of calculating the volume of main dam embankment material uses the coordinate point method of the cross-section method to calculate the cross-sectional area at each station point where the coordinate point data is X as distance and Y as elevation. At each of the two station points the cross-sectional area results at each station point will be calculated for the average cross-sectional area and then multiplied by the distance between the two station points to get the main dam embankment volume calculation results.The results of the calculation of the volume of the main dam embankment in the Cipanas Dam Development Project, Kab. Sumedang Package 3 uses the cross-section method, namely 133,967.48 m3 for main dam embankments zone 1, 71,834.86 m3 for maindam embankments zone 2a, 54,229.91 m3 for main dam embankments zone 2b, 805,398.12 m3 for main dam embankments zone 3, 60,161 .47 m3 for zone 4 main dam embankment.